sleep disorders due to neuroinfections: clinical symptoms, neurochemistry and neurophysiology V.B. Voitenkov1, N.V. Skripchenko1, Y.E. Zueva 2 - V. B. Voitenkov; N. V. Skripchenko; Y. E. Zueva (Журнал инфектологии, 2015)
In our review we present data on sleep disturbances in neuroinfections (encephalitis and meningitis), their clinical signs, neurochemistry and neurophysiology. These signs include lethargy, narcolepsy, sleep apnoe, sleep structure disruptions and may appear in acute period and as a sequelae of the disease. Reticular formation involvement seems to be the main reason for such sleep disorders. GABA and orexin systems disruption may play the key role in them. Neurophysiology evaluation of such disorders includes polysomnography, EEG-monitoring, brainstem acoustic evoked potentials and H-reflex investigation.